ANALISIS DEBIT PADA SALURAN SEKUNDER IRIGASI PELAMBIK KECAMATAN PRAYA BARAT DAYA KABUPATEN LOMBOK TENGAH - DAVID BILI; MUHAMAD YAMIN; I GUSTI NGURAH OCTOVA SEVENTILOFA (SOSIAL SAINS DAN TEKNOLOGI, 2023)
The purpose of this study is to explain the availability of water in the Pelambik irrigation secondary canals, and explain the level of efficiency of the Pelambik irrigation secondary canals. This type of research is a case study to determine the performance of the Pelambik secondary canal in the Batujai Dam, Central Lombok Regency. The results showed that water for needs ranging from processing preparation to planting was still sufficient according to the results of the analysis, where the water requirement during the processing period in October 2nd, the water debit Q = 4691,432 m3/s while the water requirement for processing NFR = 1290 m3 /sec. Irrigation efficiency level in Pelambik secondary irrigation has an average efficiency of 35%